EXPLORING THE EFFECT OF PROBLEM BASED LEARNING WORKSHEETS ON STUDENTS' MATHEMATICAL COMMUNICATION - Selvi Loviana; Tina Yunarti (Universitas Muhammadiyah Metro, 2025)
Mathematical communication skills are essential for students to develop in mathematics learning. These skills involve expressing ideas, explaining problem-solving procedures, and constructing logical arguments systematically. However, observations and interviews at SMP Negeri 9 Metro revealed that students' mathematical communication skills remain low. They struggle to write mathematical models, represent problems visually, and convert contextual situations into appropriate mathematical symbols or notations. This condition is further aggravated by teacher-centered learning and using less engaging and contextual media. This study examines the effectiveness of Student Worksheets (LKPD) based on Problem-Based Learning (PBL) in improving students' mathematical communication skills. The research employed a quasi-experimental method with a post-test only control group design. The sample consisted of two eighth-grade classes selected through purposive random sampling: class VIII F, which used the LKPD before revision, and class VIII D, which used the LKPD after revision. The research instrument was a mathematical communication test, while the data were analyzed using the Mann-Whitney test. The results showed no significant difference in students' mathematical communication skills between the classes before and after the revision of the PBL-based LKPD, with a significance value of 0.876 (> 0.05). These findings indicate that the revised LKPD has not yet fully incorporated elements that support communication skills, such as tasks promoting discussion, written and oral expression, and adequate visual representation. Therefore, future development of LKPD should integrate real-life contexts, engaging visualization, and collaborative activities to enhance students' ability to communicate mathematical ideas. Keterampilan komunikasi matematis merupakan kompetensi penting yang harus dimiliki peserta didik dalam pembelajaran matematika. Keterampilan ini mencakup kemampuan mengungkapkan ide, menjelaskan prosedur pemecahan masalah, serta menyusun argumen logis secara sistematis. Namun, hasil observasi dan wawancara di SMP Negeri 9 Metro menunjukkan bahwa kemampuan komunikasi matematis peserta didik masih rendah. Mereka mengalami kesulitan dalam menuliskan model matematika, merepresentasikan masalah secara visual, serta mengubah situasi kontekstual menjadi simbol atau notasi yang sesuai. Kondisi ini diperburuk oleh pembelajaran yang berpusat pada guru serta penggunaan media yang kurang menarik dan kontekstual. Penelitian ini bertujuan menguji efektivitas Lembar Kerja Peserta Didik (LKPD) berbasis Problem Based Learning (PBL) untuk meningkatkan kemampuan komunikasi matematis. Metode penelitian yang digunakan adalah eksperimen semu dengan desain post-test only control group. Sampel terdiri dari dua kelas VIII yang dipilih melalui purposive random sampling, yakni kelas VIII F sebagai kelompok yang menggunakan LKPD sebelum revisi dan kelas VIII D sebagai kelompok yang menggunakan LKPD setelah revisi. Instrumen penelitian berupa tes kemampuan komunikasi matematis, dengan analisis data menggunakan uji Mann-Whitney. Hasil penelitian menunjukkan tidak terdapat perbedaan signifikan antara kemampuan komunikasi matematis peserta didik pada kelas sebelum dan sesudah revisi LKPD berbasis PBL, dengan nilai signifikansi 0,876 (> 0,05). Temuan ini menunjukkan bahwa revisi LKPD belum optimal dalam memuat unsur yang mendukung pengembangan komunikasi matematis, seperti penugasan diskusi, penyampaian ide secara tertulis maupun lisan, dan representasi visual. Oleh karena itu, pengembangan LKPD selanjutnya perlu mempertimbangkan integrasi konteks nyata, visualisasi menarik, serta aktivitas kolaboratif agar peserta didik dapat berlatih mengomunikasikan ide matematika secara efektif.